Night at the Museum Research Expo: Coming Together for the Tłı̨chǫ Cultural Commons Archive ... : Tłı̨chǫ Cultural Commons Research Series, Volume 1 ... - Bourgeois, Rebecca L.; Gelderman, Karen (University of Alberta Library, 2023)
On December 6th and 7th, 2022, the Tłı̨chǫ Government Department of Culture and Lands Protection (DCLP) hosted a two day “Night at the Museum Research Expo.” This event was originally thought of as a way to introduce the Tłı̨chǫ Cultural Commons archival work to the public in Behchokǫ̀, but then grew into a larger event that showcased many aspects of Tłı̨chǫ research. Over two days, we gathered as researchers, Elders, and community members within the community museum space at Kǫ̀ Gocho (Sportsplex) in Behchokǫ̀ to celebrate, discuss, and present research being done in Tłı̨chǫ lands and culture. This booklet details these research events and represents the first of a research series documenting the archival work being done. It was inspired by the example set by our first sharing circle (detailed in this booklet) and the emphasis that the Elders put on documenting their knowledge. Suggestions for booklets as tools for documenting our research and other knowledge held within the archive were voiced by Mike ...